PERBANDINGAN HASIL DOUYIN MAKEUP LOOK PADA BENTUK MATA MONOLID DAN DOUBLE EYELIDS - Wichdati, Farah Imelda; Megasari, Dindy Sinta; Windayani, Novia Restu; Nia Kusstianti (Jurnal Tata Rias, 2026)
The development of digital beauty trends has influenced makeup techniques that emphasize eye dimension and a youthful appearance. This study aims to compare the results of the Douyin makeup look on monolid and double eyelid eye shapes. The research employed an experimental method using two models, with evaluations conducted by 30 observers using a Likert-scale observation sheet. The results indicate that monolid eyes obtained an average score of 3.45, while double eyelids achieved a higher average score of 3.60. The highest scores for both eye shapes were found in the aspect of overall visual harmony, whereas the lowest scores were observed in color gradation and soft-focus effects. The Independent Sample T-Test revealed a statistically significant difference (p < 0.05). In conclusion, double eyelid eyes produce more optimal eye makeup application results due to the presence of an eyelid crease that facilitates blending and dimensional formation. These findings may serve as a reference for makeup artists in selecting application techniques according to eye shape characteristics. Keywords: Douyin makeup look, monolid, double eyelids